Aliran-Aliran Filsafat dan Relevansinya dalam Pemikiran Modern - Siti Ulfatul Faizah; Agung Winarno; Subagyo Subagyo (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The development of philosophy from the classical to the contemporary era shows fundamental changes in the way humans understand reality with the emergence of various schools of thought that address epistemological, ontological, and ethical issues in an increasingly complex social context. This study aims to examine the contributions of key concepts from rationalism, empiricism, idealism, materialism, positivism, pragmatism, phenomenology, existentialism, Marxism, Islamic existentialism, and neopositivism, as well as assess their relevance to modern dynamics such as identity crises, technological advances, and changes in socio-economic structures. Using a conceptual approach to literature review, various previous studies were analyzed to build an integrated understanding of the position of each school of thought in the development of science and social practice. The findings show that rationalism and empiricism continue to underpin scientific methods, idealism and materialism offer different perspectives on social construction, phenomenology and existentialism deepen the understanding of subjective experience, while Marxism and pragmatism provide an analytical framework for power relations and practical action. Neopositivism continues to influence quantitative methodology, while Islamic existentialism provides a contextual moral perspective. This study emphasizes the need for an interdisciplinary approach because no single philosophical school of thought is capable of explaining reality in its entirety.